Hubungan Antara Kepuasan Kerja Dengan Motivasi Kerja Karyawan di PT Buana Karya Surya Pratama Ponorogo - Mustaqim, Hanif Rosyid; , Achmad Dwityanto, S.Psi, M.Si (2016)
This research aims to knoe is there any relationship etween the job satisfaction with employees motivation in PT Buana Karya Surya Pratama Ponorogo. The proposed hypothesis that is there is a positive relationship between the job satisfaction with the motivation of working employees at PT Buana Karya Surya Pratama Ponorogo. The sampling techniques used in this research is to use random sampling techniques, with the subject as many as 70 peoples. These studies use quantitative methods using gauge the scale of the job tisfaction and work motivation scale. Research on data analysis using SPSS Nonparametric correlation techniques with 11.8 of Spearman's, obtained coefficients of correlation 0.742 with significance (p) = 0.000; (p ≤ 0.05) which means that there is a very significant positive relationship between job satisfaction with work otivation. The effective contribution of these two variables is indicated by the value of R ² = 0.55 which means that the variables affect job satisfaction variables work motivation of 55% and 45% the rest is influenced by factors other than the variable job satisfaction. The category of job satisfaction is high with the empirical average belongs to (RE) of 124.17 and average hipotetik (RH) of 97.5. While the category work qualifies as a high motivation by the empirical mean (RE) of 122.10 and average hipotetik (RH) of 95.